Eating habits in adolescents - Kimmer, David; null, null; Kovářová, Mária (STEF92 Technology Ltd., 2018)
Background: The period of adolescence is often considered the most difficult and the most important period of human life, which includes the modulation of basic human values. In the period of adolescence, primary prevention plays an important role because this is the time when life and eating habits form. Methods: The research was carried out using a non-standardized questionnaire, which contained 52 questions. This paper presents only partial results gained from the questionnaire. The research group of respondents consisted of 1130 people living in South Bohemia, who were 15–18-years-old (the average age was 16.8 years), of which 732 (64.8%) were girls and 398 (35.2%) were boys. The research was carried out in pupils of four-year high schools, middle schools of health (MSH), middle vocational schools and vocational school institutions (VSI) in the study field cook/waiter. The statistical data analysis was carried out using the programmes SASD and SPSS. Results: Based on the chi-squared test, adolescents showed a statistically significant relationship between the type of school they attended and their beverage preferences. High school pupils mostly preferred tap water ( p < 0.001), non- flavoured natural mineral water ( p = 0.004) and tea ( p = 0.066). Positive results were shown by MSH pupils, who also preferred tap water ( p < 0.001). The worst results were shown by VSI pupils, who preferred fizzy drinks and sweetened beverages ( p < 0.001) and juices ( p < 0.001). Significant differences between sexes were found in consumption of selected food components, when girls compared to boys eat more fresh vegetables and fruits. On the contrary, boys eat more beef, pork and poultry meat, sausages, potatoes, eggs and fried foods compared to girls. There were also significant differences between students of particular types of schools. Conclusion: The results of our research are in many respects consistent with those obtained by other researchers and refer to the fact that adolescent eating habits cannot be described as ideal.
Stravovací zvyklosti u adolescentů
Keywords: eating habits; adolescent; nutrition; stravovací zvyklosti; adolescent; výživa